Modification of Barley Plant Productivity Through Regulation of Cytokinin Content by Reverse-Genetics Approaches - Holubová, Katarína; Hensel, Goetz; Vojta, Petr; Tarkowski, Petr; Bergougnoux, Véronique; Galuszka, Petr (Frontiers in Plant Science, 2018)
Barley is one of the most important cereals, which is used for breweries, animal and human feeds. Genetic manipulation of plant hormone cytokinins may influence several physiological processes, besides others stress tolerance, root formation and crop yield. In planta, endogenous cytokinin status is finely regulated by the enzyme cytokinin dehydrogenase (EC 1.5.99.12; CKX), that irreversible degrades the side chain of adenine-derived isoprenoid cytokinins. Increasing grain yield by mean of manipulation of endogenous cytokinin content was assayed by the silencing of the HvCKX1 gene. Moreover, to elucidate the putative role of HvCKX1 gene on grain production, knocked-out Hvckx1 mutant plants were generated using the RNA-guided Cas9 system. Homozygote transgenic plants with silenced HvCKX1 gene and azygous knock-out Hvckx1 mutants have been selected and analyzed. Both reduced expression of HvCKX1 gene and CKX activity were measured in different stages of barley grain development. Phenotyping of the transgenic lines revealed reduced root growth, however, plants produced more tillers and grains than azygous wild-type controls and the total yield was increased up to 15 per cent. Although plant productivity was increased, total grain biomass was decreased to 80% of WT grains. RNA-seq analysis of knock-down transgenic lines revealed that several important macronutrient transporters were downregulated in the stage of massive starch accumulation. It suggests that local accumulation of cytokinins negatively affected nutrients flow resulting in reduced grain biomass. Obtained results confirmed the key role of HvCKX1 for regulation of cytokinin content in barley.